2012
DOI: 10.1055/s-0032-1302453
|View full text |Cite
|
Sign up to set email alerts
|

Management of the Thrombosed Filter-Bearing Inferior Vena Cava

Abstract: Inferior vena cava (IVC) filter thrombosis is a complex problem. Thrombus within an IVC filter may range from an asymptomatic small thrombus to critical IVC occlusion that affects both lower extremities. The published experience of IVC thrombosis management in relation to filters is either anecdotal or limited to a small group of patients; however, endovascular treatment methods appear to be safe and effective in patients with IVC thrombosis. This review focuses on filter-related IVC thrombosis and its endovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…In our patient, the disease was complicated by an extensive area of thrombosis involving the right femoral vein and left external iliac vein, for which an IVC filter was inserted. The treatment options for such a complication could be noninvasive, such as using oral or intravenous anticoagulants, or invasive, such as using catheter-directed thrombolysis or power pulse spray [ 19 ]. Other feasible treatment options include mechanical thrombectomy and balloon venoplasty [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our patient, the disease was complicated by an extensive area of thrombosis involving the right femoral vein and left external iliac vein, for which an IVC filter was inserted. The treatment options for such a complication could be noninvasive, such as using oral or intravenous anticoagulants, or invasive, such as using catheter-directed thrombolysis or power pulse spray [ 19 ]. Other feasible treatment options include mechanical thrombectomy and balloon venoplasty [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, without the use of anticoagulants, the IVC filter can be thrombosed, creating another complex clinical problem. 12 We believed that filter removal at this time would be accompanied by a lower risk of re-bleeding and minimized the observational period without anticoagulants, because the endovascular maneuver of the filter removal would be easier and simpler than if performed later, and leaving the perforated filter in the IVC might have the potential to cause re-bleeding with trunk movement after restarting anticoagulants.…”
Section: Discussionmentioning
confidence: 99%
“…Filter retrieval should be attempted for both retrievable and permanent filters. [38][39][40] Several studies have shown safe retrieval of permanent filters using advanced techniques. [41][42][43][44] If the filter cannot be retrieved, angioplasty and placement of a self-expanding 18-to 24-mm stent across the filter may be performed to exclude the filter from the reconstructed lumen.…”
Section: Technical Considerationsmentioning
confidence: 99%